2017
DOI: 10.18632/oncotarget.20369
|View full text |Cite
|
Sign up to set email alerts
|

An integrated multigene expression panel to predict long-term survival after curative hepatectomy in patients with hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) frequently recurs even after curative hepatectomy. To develop an integrated multigene expression panel, 144 patients were randomly assigned to either discovery or validation set in a 1:2 ratio. Using surgically resected HCC specimens, expression levels of 12 candidate molecular markers were determined using quantitative reverse-transcriptase PCR. In the discovery set, an expression panel was developed according to the concordance index (C-index) values for overall survival from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The subpopulation index was used to optimize the number of markers included in the panel, and inclusion of four markers was found to be the most objectively balanced system. To maximize performance of the expression panel, a weighting using the coefficient of each constituent was employed to determine the expression index for all patients [ 19 ]. Thereafter, patients were stratified based on their expression score (1 to 3) according to the expression index, which was a more straightforward patient stratification method compared with using continuous numeric variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subpopulation index was used to optimize the number of markers included in the panel, and inclusion of four markers was found to be the most objectively balanced system. To maximize performance of the expression panel, a weighting using the coefficient of each constituent was employed to determine the expression index for all patients [ 19 ]. Thereafter, patients were stratified based on their expression score (1 to 3) according to the expression index, which was a more straightforward patient stratification method compared with using continuous numeric variables.…”
Section: Discussionmentioning
confidence: 99%
“…The larger the number of markers included in the panel, the greater the number of subpopulations that patients were clustered into with a corresponding decrease in the minimal number of patients in a subpopulation. Thus, third, we used the subpopulation index, calculated as number of constituents × the minimal patient number in a subpopulation, for each number of combinations to determine the most well-balanced number of markers to be included in the expression panel [ 19 ]. Fourth, the expression index was determined with weighting according to the coefficient in a Cox regression of each constituent.…”
Section: Methodsmentioning
confidence: 99%
“…Among these inhibitors, the SAM-uncompetitive PRMT5 inhibitor EPZ015666 has displayed effective anti-tumor activity in MCL xenograft animal models 25. Recent studies suggested that PRMT5 is upregulated in patient HCCs and may play a role in hepatocarcinogenesis 26-28, suggesting that targeting PRMT5 may have therapeutic effects on HCC. Nevertheless, effect of PRMT5 inhibitors on HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%